Dynamics of Strategic Power Interaction in Indonesia: An Analysis of Health Policy in Semarang and Makassar - Teguh Yuwono (Department of Politics and Government Science Univer, 2026)
This study examines how local power contestation and institutional dynamics influence the sustainability of Healthy City initiatives in Indonesia, focusing on a comparative analysis of Semarang and Makassar. It aims to explore how governance arrangements, leadership, and civic participation shape early patterns of policy sustainability. Drawing on a governance perspective that emphasizes state–society relations and institutional interaction, this study employs a qualitative most-similar case approach. Data were collected through preliminary semi-structured interviews with government officials, health practitioners, civil society actors, and academics, complemented by an initial review of policy documents. The findings indicate that formal policies and institutional structures alone are insufficient to sustain Healthy City programs. Makassar demonstrates a more polycentric governance model supported by a multi-stakeholder Healthy City Forum, enabling cross-sector collaboration and longer-term policy continuity. In contrast, Semarang exhibits a more top-down and sectoral governance pattern, which limits coordination and weakens sustainability. Additionally, weak accountability and hidden power relations constrain meaningful community participation in both cities. This study concludes that aligning political leadership, institutional capacity, and civic engagement is crucial for sustaining urban health initiatives. As a preliminary analysis, the findings highlight the importance of collaborative governance and suggest the need for further in-depth research.